2021
DOI: 10.1038/s41598-021-82041-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in headache characteristics with oral appliance treatment for obstructive sleep apnea

Abstract: Changes in headache characteristics in obstructive sleep apnea (OSA) patients following oral appliance treatment was investigated for the first time. Thirteen OSA patients with headaches treated with a mandibular advancement device were investigated. Level I polysomnography and Migraine Disability Assessment Questionnaire were completed before and after treatment. Various headache characteristics and concomitant conditions were analyzed. The patient was considered a headache responder when ≥ 30% reduction in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“…These data may indicate that though morning headache is associated with hypertension in patients with OSA, the causes may be multifactorial. Finally, headache in patients with OSA may be related to sleep bruxism, which may be improved by using an oral appliance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data may indicate that though morning headache is associated with hypertension in patients with OSA, the causes may be multifactorial. Finally, headache in patients with OSA may be related to sleep bruxism, which may be improved by using an oral appliance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, obesity and obstructive sleep apnea are strongly associated ( 159 ). In this respect, patients with migraine, especially older men with chronic migraine and a high BMI, seem to have a high risk of sleep apnea, whose treatment (e.g., with an oral appliance) might be beneficial in some patients ( 160 , 161 ). To date, the causal relationship between obstructive sleep apnea and migraine has not been established, although this sleep disturbance may be a trigger factor that could accelerate migraine progression ( 162 ).…”
Section: Association Of Migraine and Obesitymentioning
confidence: 99%
“…Recent research has shown that PAP therapy may increase pain tolerance and threshold [ 73 ]. Park et al [ 74 ] evaluated the change in headache prevalence in consecutive OSA patients who were treated with MAD. Eleven patients (85%) before and seven patients (54%) after treatment reported morning headache.…”
Section: Headachementioning
confidence: 99%